2012
DOI: 10.1002/jca.21206
|View full text |Cite
|
Sign up to set email alerts
|

The effective use of plerixafor as a real‐time rescue strategy for patients poorly mobilizing autologous CD34+ cells

Abstract: Plerixafor enhances CD34+ cell mobilization, however, its optimal use is unknown. We hypothesized that plerixafor could “rescue” patients in the midst of mobilization when factors indicated a poor CD34+ yield. Of 295 consecutive autologous peripheral blood mobilization attempts at our center, 39 (13%) utilized plerixafor as rescue strategy due to a CD34+ cell concentration <10/µL (median 5.95/µL, n=30), low CD34+ cell yield from prior apheresis day (median 1.06 × 106 CD34+ cells/kg, n=7), or other (n=2). Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…The median number of PB CD34+ cells after plerixafor was 42.8 cells/μl (range 7.18-91), representing a 3-fold increase of the median circulating CD34+ cell count after the first plerixafor administration. The relative increase in blood CD34+ cell concentrations after plerixafor in individual patients ranged from less than 2-fold to more than 7-fold, which is similar to other reports [46,47]. A linear correlation was shown between the PB CD34+ level and CD34+ cells/kg collected by apheresis (fig.…”
Section: Discussionsupporting
confidence: 89%
“…The median number of PB CD34+ cells after plerixafor was 42.8 cells/μl (range 7.18-91), representing a 3-fold increase of the median circulating CD34+ cell count after the first plerixafor administration. The relative increase in blood CD34+ cell concentrations after plerixafor in individual patients ranged from less than 2-fold to more than 7-fold, which is similar to other reports [46,47]. A linear correlation was shown between the PB CD34+ level and CD34+ cells/kg collected by apheresis (fig.…”
Section: Discussionsupporting
confidence: 89%
“…Many investigators [25][26][27][28][29] have shown the feasibility of a just-in-time approach, based on the day 4 CD34 þ cell level, to decide whether plerixafor should be added to an otherwise G-CSF-only mobilization to rescue patients likely to fail or have an inadequate mobilization yield. It is probable that such an approach may have a favorable cost profile; however, no convincing data, compared with an appropriately dosed chemotherapy mobilization, are available.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although patients mobilized with the routine G+P strategy received a higher CD34+ cell dose in the autograft infusate and had early platelet engraftment; no difference was noted in neutrophil engraftment. The cost of plerixafor has limited its widespread use and several centers have adopted treatment algorithms for limiting plerixafor utilization (1922, 26, 27). These algorithms are designed to identify patients at risk for suboptimal mobilization without plerixafor use.…”
Section: Discussionmentioning
confidence: 99%